Analisis Zat Gizi dan Organoleptik Olahan Sosis Ikan Gabus sebagai Pangan Alternatif Mencegah Stunting - Chaerunnimah Chaerunnimah; Aswita Amir; Retno Sri Lestari; Adriyani Adam (Jurnal Kesehatan Manarang, 2021)
The prevalence of stunting in Indonesia is still high at 30,8%. Low protein intake is one of the causes of stunting. The purpose of this study was to determine the nutritional analysis and organoleptic quality in cork fish sausages. This study used a completely randomized design with 3 repetitions. Nutrient analysis was obtained from the Luff schroll test for carbohydrates, fat test with shoxlet and protein test with micro kjedhall. Organoleptic quality with acceptance of taste, texture, color and aroma by descriptive. Research results with univariate analisis were the highest nutrient content of protein and carbohydrate in formula F1 (100%) is protein (16.71%) and carbohydrate (20.14%) and the highest fat content in formula F3 (60%) is as much as (18.52%). The most preferred organoleptic quality for aroma and taste is in formula F1 (100%), texture is in formula F2(80%) and the most preferred color is in formula F3 (60%). The recommendation for prevent stunting can be used F1 formula.